Pengaruh konsentrasi bakteri entomopatogen Bacillus thuringiensis terhadap mortalitas larva kumbang tanduk (Oryctes rhinoceros) secara in vitro - Ramadhani, Suci; Pramono, Sudi; Purnomo, Purnomo; Sudarsono, Hamim (Universitas Lampung, 2026)
The rhinoceros beetle (Oryctes rhinoceros L.) is a major pest of oil palm that can reduce production and even cause mortality in immature plants. An environmentally friendly alternative for its control is the use of entomopathogenic bacterium Bacillus thuringiensis (Bt). This study aimed to determine the effect of different Bt concentration on the mortality of O. rhinoceros larvae, identify the most efficient concentration, and estimate the lethal concentration (LC50), and lethal time (LT50). The experiment consisted of six treatments (0%, 4%, 5%, 6%, 7%, and 8%) with four replications. Observed variables included morphological changes, larval mortalty, LC50, and LT50 values. The results showed that Bt had a significant effect on larval mortality. The 7% concentration was the most efficient, resulting in 98.8% mortality at 14 days after application (DAA) with the fastest LT50 of 7 days. The 6% and 8% treatments also achieved 100% mortality at 20 DAA but had longer LT50 (9 days). Symptoms of infection were characterized by larval bodies becoming darkened, softened, and emitting a foul odor. It can be concluded that the 7% Bt concentration was the most efficient in controlling O. rhinoceros larvae in vitro and has potential as a biological control agent to replace chemical insecticides.